Oxidation and molecular properties of microcystin-LR, microcystin-RR and anatoxin-a using UV-light-emitting diodes at 255 nm in combination with H2O2 - Park, Jeong-Ann; Yang, Boram; Jang, Mi; Kim, Jae-Hyun; Kim, Song-Bae; Park, Hee-Deung; Park, Hyun-Mee; Lee, Sang-Hyup; Choi, Jae-Woo (ELSEVIER SCIENCE SA, 2019)
On the use of UV light emitting diodes (UV-LEDs), emitting at 260-290 nm, has attracted attention for treating cyanotoxins, although most previous studies related with UV/H2O2 process have been used conventional mercury UV lamp (lambda= 254 nm). Therefore, the aim of the study was to investigate the UV-LEDs, having a wavelength of 255 nm, coupled with H2O2 process for the removal of microcystin-LR (MC-LR), microcystin-RR (MCRR), and anatoxin-a (ANTX) and to verify the degradation kinetics, mechanism and impact of water quality parameters in relation to their molecular properties. Among three UV-LEDs (lambda= 255, 266, and 280 nm), the shortest one was the most effective to remove MC-LR coincided with its decadic molar absorption coefficient. The degradation rate constants of MC-LR, MC-RR, and ANTX were 0.0644, 0.0241, and 0.0076 cm(2) mJ(-1), respectively, during the UV-LED/H2O2 process. For MC-LR and MC-RR degradation, reaction with % OH is a major mechanism along with direct photolysis as a minor factor. ANTX degradation is predominantly attributed to center dot OH. The second-order rate constant for ANTX is one order of magnitude lower than others because ANTX is recalcitrant to oxidation. The MC-LR degradation occurred at the diene and aromatic ring of Adda, Mdha, and amide bond and the main reactive oxidation site of MC-RR was the Adda chain. In contrast, photo-oxidation transformed ANTX to higher molecular weight compounds via polymerization instead of degradation. When MCLR, MC-RR, and ANTX were co-present, lower concentration of dissolved organic carbon and higher acidity with bicarbonate was favorable to remove MC-LR and MC-RR according to their scavenging factors and reaction with CO3 center dot-. However, ANTX is relatively resistant to degradation at pH 3.2.